History of carcinoid and pathology Contributions of Siegfried Oberndorfer to pathology and evolution of carcinoid - Dogan, Hanzade; Hot, Inci (Polish Journal of Pathology, 2010)
The famous pathologist Siegfried Oberndorfer was born in Munich, Germany, in 1876, studied medicine at the University of Munich, and became the youngest Jewish physician to be appointed to its faculty (1907). He carried out innovative studies in the fields of pathology and evolution of carcinoid as the chair of the Department of Experimental Pathology at the University of Istanbul in Turkey, where he was a Jewish refugee escaping from the political situation in Germany before the Second World War with the rise of Nazism. This paper deals with Oberndorfer’s very valuable contributions to the Department of Pathology of Istanbul University in Turkey and seeks to confirm his well-deserved place in the universal medical field of pathology and discovery of the carcinoid tumour.